Impact of newborn screening for very‐long‐chain acyl‐CoA dehydrogenase deficiency on genetic, enzymatic, and clinical outcomes. Issue 3 (8th April 2019) - Bleeker, Jeannette C.; Kok, Irene L.; Ferdinandusse, Sacha; van der Pol, W. Ludo; Cuppen, Inge; Bosch, Annet M.; Langeveld, Mirjam; Derks, Terry G. J.; Williams, Monique; de Vries, Maaike; Mulder, Margot F.; Gozalbo, Estela R.; et al.
Abstract: Most infants with very‐long‐chain acyl‐CoA dehydrogenase deficiency (VLCADD) identified by newborn screening (NBS) are asymptomatic at the time of diagnosis and remain asymptomatic. If this outcome is due to prompt diagnosis and initiation of therapy, or because of identification of individuals with biochemical abnormalities who will never develop symptoms, is unclear. Therefore, a 10‐year longitudinal national cohort study of genetically confirmed VLCADD patients born before and after introduction of NBS was conducted. Main outcome measures were clinical outcome parameters, acyl‐CoA dehydrogenase very long chain gene analysis, VLCAD activity, and overall capacity of long‐chain fatty acid oxidation (LC‐FAO flux) in lymphocytes and cultured skin fibroblasts. Median VLCAD activity in lymphocytes of 54 patients, 21 diagnosed pre‐NBS and 33 by NBS was, respectively, 5.4% (95% confidence interval [CI]: 4.0‐8.3) and 12.6% (95% CI: 10.7‐17.7; P  < 0.001) of the reference mean. The median LC‐FAO flux was 33.2% (95% CI: 22.8‐48.3) and 41% (95% CI: 40.8‐68; P  < 0.05) of the control mean, respectively. Clinical characteristics in 23 pre‐NBS and 37 NBS patients revealed hypoglycemic events in 12 vs 2 patients, cardiomyopathy in 5 vs 4 patients and myopathy in 14 vs 3 patients. All patients with LC‐FAO flux <10% developed symptoms. Of the patients with LC‐FAO flux >10% 7 out of 12 diagnosed pre‐NBS vs none by NBS experienced hypoglycemic events. NBS has a clear beneficial effect on the prevention of hypoglycemic events in patients with some residual enzyme activity, but does not prevent hypoglycemia nor cardiac complications in patients with very low residual enzyme activity. The effect of NBS on prevalence and prevention of myopathy‐related complications remains unclear.